2016
DOI: 10.9745/ghsp-d-16-00165
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Residual Spraying Delivery Models to Prevent Malaria: Comparison of Community- and District-Based Approaches in Ethiopia

Abstract: Integrating indoor residual spraying into the institutionalized community-based health system in 5 districts was more efficient than the district-based model and did not compromise quality or compliance with environmental standards.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…In term of cost analysis, one study of malaria in Ethiopia compared cost data for community- based intersectoral IRS and traditional district “vertical” IRS [ 73 ]. This study did before-after analysis of overall cost, coverage, cost per structure sprayed, and cost per person protected.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In term of cost analysis, one study of malaria in Ethiopia compared cost data for community- based intersectoral IRS and traditional district “vertical” IRS [ 73 ]. This study did before-after analysis of overall cost, coverage, cost per structure sprayed, and cost per person protected.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 50 articles, intersectoral collaboration with an intervention to mobilize community and health education was the most common. The interventions implemented through the collaboration between the sectors varied from providing human or financial resources, designing to executing an intervention, developing policy and mobilizing communities (24 studies) [ 30 , 32 , 35 , 43 – 45 , 47 50 , 53 58 , 60 65 , 68 , 72 ], followed by diagnosis and treatment (12 studies) [ 35 , 36 , 39 43 , 49 , 52 , 68 – 71 ], prevention method (IRS and LLINs distribution (11 studies) [ 31 , 35 37 , 39 , 41 , 43 , 66 68 , 73 ], surveillance, monitoring and evaluation (nine studies) [ 35 , 38 42 , 52 , 68 , 69 ], mass drug administration (four studies) [ 48 , 72 , 75 , 76 ], cross border collaboration (four studies) [ 35 , 40 , 43 , 52 ], two studies for research [ 40 , 51 ] and one study for advocacy and legislation […”
Section: Resultsmentioning
confidence: 99%
“…Eighteen studies reporting IRS coverage were identified in the review [ 27 , 58 , 59 , 66 - 80 ]. Coverage estimates were more commonly obtained through post-campaign household surveys [ 27 , 66 , 69 - 71 , 74 , 76 , 79 , 80 ] than routine IRS program records [ 58 , 59 , 68 , 72 , 73 , 77 ] or study records [ 75 ]. Two studies reported coverage from both household surveys and program records [ 67 , 78 ].…”
Section: Resultsmentioning
confidence: 99%
“…To reflect targeting of IRS at areas prone to outbreaks or identified as transmission sources the reference scenario assumed deployment in 50% of HFCAs. As transmission is further reduced across eliminating countries implementation of IRS might be shifted further down to HFCA level [29]. This would change the level and the distribution of costs and could be further explored with the costing model.…”
Section: Reference Implementation Scenariosmentioning
confidence: 99%